SISTEM PENGAMAN PINTU OTOMATIS DENGAN MIKROKONTROLER ARDUINO DAN MODULE RF REMOTE - Selamet Samsugi; Achmad Irvandi Yusuf; Fika Trisnawati (Universitas Teknokrat Indonesia, 2020)
This final task report aims to design and Meng-implementasikan a series that serves to security and follow technology installed on the security of the door and controlling the existing doors of the door such as the Module key of the RF Remote Arduino that is for opening and closing doors. And discussing about RF Remote which is used to detect a frequency that will be output and input for the Arduino microcontroller. To control the Arduino microcontroller used the C and Arduino programming languages by using the Arduino software. The way this tool works is when people want to be quick and concise in opening and closing its doors. The door that has been on the security of the RF Remote will not be in the process, if the RF Remote button does not press on the password that has been known on the microcontroller, if the existing door lock RF Remot will turn on the opening and closing doors. In the door there is also a sound mark when in the Sensor Switch does not get a hard enough clearance or emphasis, if the microcontroller does not GET the ID for 5 seconds and automatically instantly Sounds The buzzer or sound of the alarm tone if the door is forced to open or close. The RF Remote Module receives a frequency signal and is connected to the Solenoid door lock, and is processed by the Arduino and then to through the relay to connect the line current on the door lock Solenoid and Servo Motor